The Influence Ecotourism on The Economy of Citizen Community in The Situ Tunggilis Bogor District - Nugraha, Rizki Nurul; Hidayah, Nurul (Jurnal Manajemen Pelayanan Hotel, 2022)
Ecotourism is a tourism sector that has the potential as a supporter of the national economy, from ecotourism it can also be used by local governments to increase their own local revenue. This study aims to determine the effect of ecotourism in terms of location, attractiveness, facilities, and accessibility to the economy of the community in the Situ Tunggilis area, Bogor district. The research method used is a descriptive qualitative method with data collection through literature studies, interviews, observations and documentation. The results showed that 70.5% of the traders in the Tunggilis situ, Bogor district, were local people, namely the people from the village of Setu Sari. Then, based on the average monthly income, most of the traders have an income of Rp. 1,000,000 – Rp. 5,000,000. This shows that the income level of the people in the Situ Tunggilis area is classified as moderate. Thus, the existence of the Tunggilis area can affect the economy of the surrounding community. This can be seen from Situ tunggilis which can be a place of livelihood for the people in the Situ tunggilis area, namely as food traders (snacks), toy traders, fish traders, fishermen, tour boat carriers, and parking attendants. And the income of the community is increasing along with the increasing number of tourists who come to the Tunggilis area. So that in line with the better conditions of Situ Tunggilis ecotourism which can be measured from location, tourist attraction, accessibility and facilities, it can invite many tourists who come to the Situ Tunggilis area, Keywords: Ecotourism, Community Economy, Situ Tunggilis